Aplikasi art terapy di sekolah berdasarkan golongan darah - Christine Masada Hirashita Tobing; Eva Yuliana (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
Children are very passionate living his life, environment isn’t understand child development yet, thus decreasing spirit of his life developing, curiosity and empathy for his environment. Passion of life's joy developed through talent of interest based blood type, determining a sense of interest in a particular activity, for there is a love to do it. Art is a fun activity increases productivity of life, according to talent and interest without being forced. Art as a therapy application to solve student problems in school related to personal, social, love, discipline, law, and religion. Descriptive qualitative methods, surveys, case studies, experiments applying individual counseling services, content mastery, and groups. The survey results, case studies and experiments, based blood type, better to map the sense of art, talent and interests of the child, correlated sense of art with the right service for its Therapeutic Art Application, motivation to make problem solving counseli.